2021
DOI: 10.1186/s12917-021-02982-y
|View full text |Cite
|
Sign up to set email alerts
|

Donkey-derived anti-CDV IgG, as a passive immunotherapy agent, can effectively increase survival rates of the experimental CDV-infected dogs

Abstract: Background Humoral immunity plays an important role in the prevention of canine distemper. Anti-CD virus (CDV) antibody has strong antiviral activity and is widely used in the treatment of CD. However, with the increase of CD cases, the availability of therapeutic CD antibody fell short of the clinical needs. Results The high-titer antiserum with the high-titer neutralizing activity against CDV was obtained from the donkeys (Dezhou Donkey) immunize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…All inclusion and exclusion criteria for study animals were independently verified by an evaluation criteria committee. In addition, the breed, body weight, and age distributions of the dogs in our study were similar to those reported in previous studies that recorded dogs diagnosed with non-neurological and neurological distemper [8,10,23]. The comparison of control group and placebo group allows for the identification of possible effects of the intervention medication (AgNPs) that go beyond the normal recovery capacity of the patients, which is known to be low in patients diagnosed with neurological distemper [24].…”
Section: Strengthssupporting
confidence: 83%
See 4 more Smart Citations
“…All inclusion and exclusion criteria for study animals were independently verified by an evaluation criteria committee. In addition, the breed, body weight, and age distributions of the dogs in our study were similar to those reported in previous studies that recorded dogs diagnosed with non-neurological and neurological distemper [8,10,23]. The comparison of control group and placebo group allows for the identification of possible effects of the intervention medication (AgNPs) that go beyond the normal recovery capacity of the patients, which is known to be low in patients diagnosed with neurological distemper [24].…”
Section: Strengthssupporting
confidence: 83%
“…Outbreaks of CDV have also been reported in animals ranging from stray dogs to zoo animals such as wild tigers and giant pandas, highlighting the zoonotic and spillover characteristics of CDV [40]. Some antiviral drugs have been reported to have an effect in vitro, but none of them have demonstrated clinical efficacy in dogs diagnosed with non-neurological and neurological distemper [18][19][20][21][22][23]. The development of new antiviral drugs based on nanotechnology could offer a promising short-term option.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations